27.1k views
0 votes
Please answer the quesion below.

Show your work please thanks. = )

Please answer the quesion below. Show your work please thanks. = )-example-1
User GluePear
by
5.2k points

1 Answer

5 votes

Hi GlaxyCraft4991,

Solution:

9/2(8−x) + 36 = 102 − 5/2(3x+24)

(9/2)(8) + (9/2) (−x) + 36= 102 + −15/2x + −60 (Distribute)

36+ −9/2x + 36 = 102 + −15/2x + −60

(−9/2x) + (36 + 36) = (−15/2x) + (102 + −60)(Combine Like Terms)

−9/2x + 72 = −15/2x + 42

−9/2x + 72 + 15/2x = −15/2x + 42 + 15/2x

3x + 72 = 42

3x + 72 − 72 = 42 − 72

3x = −30

3x/3 = −30/3

x = -10

Answer:

x = -10

User TreyE
by
5.6k points